Menyoktek = Drop Out? Sebuah Strategi Untuk Menegakkan Integritas Akademik Mahasiswa - Rahmi Juwita (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
Abstract : In the era of the development of science and the addition of new departments and universities both in Indonesia and the world, research on integrity is increasing. One of the studies mentioned that many integrity violations were committed by students during exams. Enforcement of integrity can be started with strict regulations for violators. This research aims to explore the dropout sanction for students who cheat as one of the strategies to enforce students' academic integrity. The research uses a case study method with interviews, observations, and documentation studies as data collection techniques. Robert K. Yin's six steps of case study research were used in this study, namely plan, design, prepare, collect, analyze, and share. Data analysis uses data validity by comparing all data obtained with three collection techniques, classifying data based on research questions, combining the data obtained in the form of tables, and finally making conclusions based on the data that has been obtained. The results showed that the impact of dropout sanctions for students who cheat is the emergence of awareness related to integrity values such as honesty, responsibility, the emergence of student confidence in working on exam questions, and being able to reduce the number of students who cheat on exams.